Support for Syria's civil society - misguided and ineffective: Without military action, international support will continue to be of no avail - Petra Becker (Stiftung Wissenschaft und Politik (SWP), 2014)
Three-and-a-half years after the start of the peaceful protests in Syria the civil actors have been marginalised. The picture is dominated by a broad range of different militias. Few of them have a vision of Syria as a country based on pluralism and united in territorial, ethnic and denominational terms. Half of the population has fled abroad or has been displaced within the country. Millions of internal refugees are dependent on humanitarian aid. In view of the international military campaign against the group which calls itself Islamic State, the Western supporters of the opposition urgently need to review their original strategy, which focused almost entirely on promoting civilian structures. (SWP Comments)
Keywords: 320